Zastosowanie reakcji Fentona w technologii osadów ściekowych = The use of Fenton reaction in the technology of sewage sludge - Kowalczyk, Mariusz; Kamizela, Tomasz; Parkitna, Kamila; Milczarek, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The presented publication is a review of the literature on the use of the Fenton reaction in the technology of sewage sludge. Application of advanced oxidation provides opportunities for pollution reduction and improvement of the technological characteristics of the sediments. Fenton reaction may be an effective factor in conditioning both municipal sludge and industrial purposes against dehydration.
Keywords: osady ściekowe; reakcja Fentona; odwadnianie; redukcja zanieczyszczeń; ultradźwięki; sewage sludge; Fenton reaction; dewatering; reduction of pollution; ultrasound